Role of carboxytherapy in localized lipolysis: a clinical and radiological study - Azza G.A Farag; Alaa H Maraee; Ashraf A Zytoon; Wafaa A Shehata; Shahlaa Abd El Reheim Essa (Wolters Kluwer Medknow Publications, 2019)
Background Localized obesity is a result of accumulation of adipose tissue present in small quantities in specific area. It is an important issue to search for novel noninvasive fat elimination modalities which help in body contouring. Objective To estimate the efficacy as well as safety of subcutaneous injection of CO2 in management of localized fat deposits. Patients and methods This interventional study was conducted on 34 females)22-45years old) having localized fat deposits in abdomen, chin, arm, and thigh. For all history and clinical examination including circumferential tape measurements were done. Digital photographic registration and ultrasound measurements of subcutaneous fat thickness, as well as circumferences of the treated areas before and after eight carboxytherapy sessions (once/week) were performed. Results There were observed improvement in carboxytherapy treated areas (abdomen, chin, arm, and thigh) in all studied subjects indicated by significant decrease in circumferences of abdomen (P<0.0001), arms (P=0.0003), and thighs (P<0.0001), and ultrasound fat thickness measurements in abdomen (P≤0.0001), chin (P=0.012), arms (P=0.0004), and thighs (P<0.0001). This improvement was achieved in arm (P=0.0004) and chin (P=0.012) better than abdomen and thighs. Half of our patients (17, 50%) recorded an excellent degree of satisfaction, the highest satisfaction rate was among patients who had lipolysis in the chin region (P=0.027). Pain (mild and moderate) and ecchymosis were the only observed adverse effects. Conclusion Carboxytherapy may be an effective method that could be used in the management of localized obesity, without remarkable adverse effects. Treatment of localized obesity by CO2 sessions once weekly for 8 weeks has a significantly better outcome in arms and chin than in abdomen and thighs.